Slower elimination of tofacitinib in acute renal failure rat models: Contribution of hepatic metabolism and renal excretion - Bae, Sung Hun; Chang, Sun Young; Kim, So Hee (Pharmaceutics, 2020)
Tofacitinib is a Jak inhibitor developed as a treatment for rheumatoid arthritis. Tofacitinib is metabolized mainly through hepatic CYP3A1/2, followed by CYP2C11. Rheumatoid arthritis tends to increase renal toxicity due to drugs used for long-term treatment. In this study, pharmacokinetic changes of tofacitinib were evaluated in rats with gentamicin (G-ARF) and cisplatin-induced acute renal failure (C-ARF). The time-averaged total body clearance (CL) of tofacitinib in G-ARF and C-ARF rats after 1-min intravenous infusion of 10 mg/kg was significantly decreased by 37.7 and 62.3%, respectively, compared to in control rats. This seems to be because the time-averaged renal clearance (CLR) was significantly lower by 69.5 and 98.6%, respectively, due to decreased creatinine clearance (CLCR). In addition, the time-averaged nonrenal clearance (CLNR) was also significantly lower by 33.2 and 57.4%, respectively, due to reduction in the hepatic CYP3A1/2 and CYP2C11 subfamily in G-ARF and C-ARF rats. After oral administration of tofacitinib (20 mg/kg) to G-ARF and C-ARF rats, both CLR and CLNR were also significantly decreased. In conclusion, an increase in area under plasma concentration-time curves from time zero to time infinity (AUC) of tofacitinib in G-ARF and C-ARF rats was due to the significantly slower elimination of tofacitinib contributed by slower hepatic metabolism and urinary excretion of the drug.
Keywords: Acute renal failure; Cisplatin; Creatinine clearance; Gentamicin; Hepatic CYP3A1(23); Nonrenal clearance; Pharmacokinetics; Renal clearance; Tofacitinib